Marketing capability and firm performance: the mediating role of resource orchestration capability - Frank Agyemang Duah; Bylon Abeeku Bamfo; John Serbe Marfo (Cogent Social Sciences, 2024)
AbstractThis study investigates the intricate relationship between marketing capabilities, resource orchestration capacity, and firm performance within the context of contemporary business environments. A quantitative research approach was employed in this study. Drawing on a sample of 379 firms, the study employed PLS-SEM to assess the impact of marketing capability on a firm’s performance and explore the mediating role played by resource orchestration capability in this dynamic. A structured questionnaire was developed and administered among autonomous business-to-consumer (B2C) firms operating in the service and manufacturing industries. A convenience sampling technique was deployed in this study. This research contributes to the growing body of knowledge on marketing strategy by shedding light on the underlying mechanisms through which marketing capability influences firm performance. Practically, the study provides strategic insights for firms aiming to enhance their marketing effectiveness and overall performance by optimizing their resource orchestration capabilities. The implications of this research extend to marketing professionals, strategists, and scholars seeking a deeper understanding of the nuanced interplay between marketing capabilities, resource orchestration, and firm performance in the contemporary business landscape.